COMMENTS ON GUIDELINES OF THE TASK FORCE FOR DIAGNOSIS AND TREATMENT OF CHRONIC HEART FAILURE OF THE EUROPEAN SOCIETY OF CARDIOLOGY (2005) - V. V. Yakusevich (Рациональная фармакотерапия в кардиологии, 2016)
.